Development of Interactive Digital Media Based on Values of Tolerance and Respect for Diversity for Islamic Religious Education in Junior High Schools - Muhammad Mujahwirul Ilma; Himma Ulya Warda; Muhammad Wazid Husni; Alfiyan Chasanul Muna; Nazih Sadatul Kahfi (Journal of Education and Teacher Training Innovation, 2026)
This study aims to develop an interactive learning media in the form of a 3D animated video using Plotagon Story to enhance student engagement in Islamic Religious Education and Character Education at the junior high school level, particularly in promoting values of tolerance and respect for diversity. The research employed a Research and Development (R&D) approach using the ADDIE model. Data were collected through observation, interviews, questionnaires, and documentation involving 24 eighth-grade students and three expert validators at SMP Nurul Islami, Semarang City, during the second semester of the 2024/2025 academic year. Data were analysed using a mixed-methods approach combining thematic analysis for qualitative data and a paired t-test for quantitative data. The results indicate that the media is highly valid (88.6%), practical (92% of students found it easy to use), and effective in improving student engagement across affective, cognitive, and behavioral domains. These findings support multimedia learning and student engagement theories, suggesting that narrative animation can serve as an effective tool for internalizing religious values within a socially relevant context.